LAW ENFORCEMENT AGAINST TRADEMARK INFRINGEMENT IN INDONESIA: Volume 2024, pp. 35-46 - Indrawati, Etty (MATTER: International Journal of Science and Technology, 2024)
Trademark as part of intellectual property rights is one of the most important elements in the business world. Trademark protection is one form of legal certainty required by investors, both domestic and foreign. The legal certainty also expects law enforcement against trademark infringement. The number of trademark infringement that occurred in Indonesia from 2015 to 2023 shows an increasing trend. The purposes of this research are to explore and analyze regarding the cause of trademark infringement and to investigate how efforts should be made to solve and reduce the number of trademark infringements in Indonesia. This research is normative legal research underpinned by interviews as well as through library research by tracing secondary data, using documentation methods and instrument in the form of document studies. Interviews were conducted with resource persons using interview guidelines. Then, data were analyzed using qualitative analysis.The result shows that the reason for trademark infringement is economic reasons. The offending party has bad intentions and assumes that the business whose trademark is to be imitated has good potential and person concerned can obtain a reasonable profit (good turnover potential) if using the same or similar trademark. The second is the party whose trademark is used by another party without rights needs to make a complaint about the trademark infringement because the violation/ infringement of intellectual property rights (including trademark infringement) is a complaint of violation that must be reported by the injured party to the law enforcer. This research is expected to provide input to the government and law enforcer in Indonesia related to law enforcement against trademark infringement that occurred in Indonesia.